1996
DOI: 10.1172/jci118409
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of methotrexate polyglutamates in lymphoblasts is a determinant of antileukemic effects in vivo. A rationale for high-dose methotrexate.

Abstract: Methotrexate (MTX) is one of the most widely used drugs for the treatment of childhood acute lymphoblastic leukemia (ALL) and is commonly given in high doses. However, the rationale for high-dose MTX (HDMTX) has been challenged recently. To determine whether higher MTX polyglutamate (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
126
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(137 citation statements)
references
References 35 publications
(41 reference statements)
10
126
1
Order By: Relevance
“…12 Thus, the positive relationship between TGN levels and longchain MTX-PG concentrations we observed is consistent with their inhibition of de novo purine synthesis and increased PRPP formation.…”
Section: Resultssupporting
confidence: 84%
“…12 Thus, the positive relationship between TGN levels and longchain MTX-PG concentrations we observed is consistent with their inhibition of de novo purine synthesis and increased PRPP formation.…”
Section: Resultssupporting
confidence: 84%
“…Hence, decreased MTX doses could reduce the antileukemic effect of MTX. 20,21 In addition, MTX dose reduction would limit penetration of MTX into the CNS, 22 which could increase the risk of CNS relapse. Supporting the clinical significance of high systemic MTX exposure, Evans et al 23 found that pharmacokinetically guided MTX dosage to achieve higher MTX concentration in patients with rapid clearance of the drug lead to a better outcome.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The method for quantitating DNPS was modified to yield higher overall median values when compared with the method previously used to quantitate DNPS in ALL blasts. 7,9 However, the previously observed lineage differences in DNPS (T-ALL greater than B-lineage ALL) remained evident with the current DNPS assay.…”
Section: Measurement Of Purine Bases and Rate Of Dnps In Bone Marrow mentioning
confidence: 99%